Teknik Kejut SUhu untuk Mempercepat Proses Produksi Kepiting Bakau (Scylla spp) Cangkang Lunak (Soft Shell crab) - Ridwan Ridwan; Afandi Saputra (Jurnal Airaha, 2012)
Soft Shell Crab cultivation or the most popular with moulting crab is new commodity was never acquainted by society during have marked potency is very wide, with technology and very easy for future is very brilliant. With can rise economical in farmer and fisherman at common. Production process soft sell crab have some technical namelly cutting walk feet and twezers tan can stimulate mangroove crab for moulting yet influence from environment can quickly process onccurred themperature chance is very extreem. Experiment is doing decine exteem themperature on breed mangroove crab at 10 0C, 15 0C and 20 0C. Observation is during breed include crab amoud that moulting and survival rate. From data at by means of control ( 0% ), themperature 10 0C ( 20% ),themperature 15 0C ( 30% ) and at treatment 20 0C (70%) exactly SR value in control is 100% themperature treatmen 20 C (90%), themperature 15 0C(70%) dan themperature 10 0C(40%).